Operationalising Regional Cooperation for Infectious Disease Control: A Scoping Review of Regional Disease Control Bodies and Networks - Anna Durrance-Bagale; Manar Marzouk; Sunanda Agarwal; Aparna Ananthakrishnan; Sarah Gan; Michiko Hayashi; Beth Jacob-Chow; Koh Jiayun; Lam Sze Tung; Hala Mkhallalati; Sanjida Newaz; Maryam Omar; et al. (Kerman University of Medical Sciences, 2022)
Background  The rapid spread of the coronavirus disease 2019 (COVID-19) pandemic demonstrates the value of regional cooperation in infectious disease prevention and control. We explored the literature on regional infectious disease control bodies, to identify lessons, barriers and enablers to inform operationalisation of a regional infectious disease control body or network in southeast Asia.Methods  We conducted a scoping review to examine existing literature on regional infectious disease control bodies and networks, and to identify lessons that can be learned that will be useful for operationalisation of a regional infectious disease control body such as the Association of Southeast Asian Nations (ASEAN) Center for Public Health Emergency and Emerging Diseases.Results  Of the 57 articles included, 53 (93%) were in English, with two (3%) in Spanish and one (2%) each in Dutch and French. Most were commentaries or review articles describing programme initiatives. Sixteen (28%) publications focused on organisations in the Asian continent, with 14 (25%) focused on Africa, and 14 (25%) primarily focused on the European region. Key lessons focused on organisational factors, diagnosis and detection, human resources, communication, accreditation, funding, and sustainability. Enablers and constraints were consistent across regions/organisations. A clear understanding of the regional context, budgets, cultural or language issues, staffing capacity and governmental priorities, is pivotal. An initial workshop inclusive of the various bodies involved in the design, implementation, monitoring or evaluation of programmes is essential. Clear governance structure, with individual responsibilities clear from the beginning, will reduce friction. Secure, long-term funding is also a key aspect of the success of any programme.Conclusion  Operationalisation of regional infectious disease bodies and networks is complicated, but with extensive groundwork, and focus on organisational factors, diagnosis and detection, human resources, communication, accreditation, funding, and sustainability, it is achievable. Ways to promote success are to include as many stakeholders as possible from the beginning, to ensure that context-specific factors are considered, and to encourage employees through capacity building and mentoring, to ensure they feel valued and reduce staff turnover.